The evolution of the social understanding of ethnic entrepreneurship: results from a bibliometric analysis of the literature. (1st January 2013) - Ganzaroli, Andrea; Orsi, Luigi; De Noni, Ivan
There is growing attention toward the role of ethnic entrepreneurship as a potential source of social integration and economic growth. Despite this recent interest, there is in fact a long tradition of studies focusing on ethnic entrepreneurship. Furthermore, there are also a number of qualitative literature reviews that attempt to systematise the main findings in this field of study. We contribute to existing literature by providing a more objective representation of how this concept has evolved on the basis of a bibliometric review of the literature. Our results are based on a sample of 102 publications published on this topic since 1990. Our main contribution is to show that the concept of ethnic entrepreneurship has evolved into three phases. In the first phase, scholars focused mainly on cultural factors in order to explain the differences in entrepreneurship across ethnic communities. In the second phase, the focus shifted toward the structure of opportunities available in the host society. Nowadays, scholars are focusing on the role of networking and embeddedness, and on the creation of seedbed conditions for the development of ethnic entrepreneurship in metropolitan areas.